Pregnant Revisions Information Center for Maternal and Child Welfare in the Baghdad City about Benefit of Colostrum toward the New Born Baby - Abdul Mahdi Hassan (College of Nursing,University of Mosul, 2013)
Background and aim: The first food for the baby after birth is colostrums. Therefore, the study aims to lays the importance of research in the identification information on the pregnant mother to the importance of colostrum, which is the first vaccine for her baby, which shields them from more than 28 diseases. Materials and method: purposive sample study included 150 pregnant mothers who visiting the center of maternity and child care in the Sheikh Omar and care center in Al- Elwya Teaching Hospital, and Baghdad Teaching Hospital where the sample collected way Randomly and interview style dish and apply the Questionnaire form designed for this purpose based on scientific sources and previous studies for the period from 8/11/2011 to 15/1/2012. The validity through a panel review of experts. Data were analyzed using frequency distribution and percentage. Results : the results show that 96% of respondents are housewives, while the proportion of female employees make up only 4%.Accounted pregnant women at the first time revisions ratio of 24% of respondents while the percentage delivered women, the 76%. As for the place of birth for the delivered women only figure was 38% for the birth of the house as well as the same percentage for the birth of the hospital. Conclusion: The study that breastfeeding is the best source of nutrition for a healthy term infant. Human milk is human specific and contains nutrients that are essential for the proper growth and development of the newborn. For more, breast milk is beneficial to both infant and mother. Key word: Pregnant women, benefit of colostrum, colostrum, New Born baby.